(untitled) (Studia Prawnicze / The Legal Studies, 1964)
The institution of a contractual penalty occupies not central but one of the key places in the problems of contractual liability in the socialized turnover. However, this is not a creation of socialist law but one of the oldest legal institutions. Its seeds can be seen at the very origins of the contractual relationship system formed on the basis of the desire of the perpetrator and then the “perfidious” contractual debtor to avoid revenge and execration (exsecratio) through a redemption offer. This redemption motive which lay at the cradle of the contractual penalty institution was gradually replaced with the motive for securing the turnover. It was precisely this purpose that the parties sought when establishing certain material consequences (sanctions) in the contract they had entered into, if any party violated the obligation arising from the signed contract. In capitalist law, along with the general motive for securing the turnover, a more specific motive for the exclusion of the procedural risk is clearly heard — in the interests of an unsatisfied creditor. This motive expressed in releasing the creditor from the obligation to prove the losses caused as a result of the debtor’s failure to fulfil the obligation comes to the fore. It leads to some degradation of the contractual penalty role in the economic turnover. This so-called degradation is indicated with the fact that the contractual penalty is recognized by a positive law (art. 74 — 90 of the Polish Code of Obligations) as one of the five “additional contractual preliminaries” along with a down payment, a contractual right of withdrawal, compensation and interest due for a late performance of a monetary obligation. In socialist law, the institution of contractual penalty was the main civil law measure for strengthening the contractual discipline in relations between socialist organizations. Due to the wide spread of this institution — in the absence of the uniform legal settlement and the variety of its functions in the civil law of the socialist society — it is necessary to carry out a systematization of a contractual penalty institution. There are reasons to believe that four types of contractual penalty are available in the Polish People’s Republic as well as in Soviet law: 1) alternative, 2) exclusive, 3) compatible and 4) offset. The first type regulated by Art. 82 — 85 of the Code of Obligations is a basis for a provision according to which the creditor is given the right of choice: to demand the penalty payment or to refuse it and recover damages in accordance with general practices. The second type regulated by Art. 531 of the Commercial Code excludes the possibility to recover damages on a common basis in the event of a contractual penalty imposition. The third type provided for by some specific regulations (for example, by Decree on railway freight and passenger transport dated 24 December 1951, Art. 108 — Journal of laws No. 4, chapter 7 of 1953) grants the right to recover penalties regardless of compensation for losses on a common basis. The fourth type established by the socialist turnover law of the Polish People’s Republic (for example, Basic Terms of Delivery in State Turnover, § 83 — 84, Monitor Polski, No. 34, chapter 172 of 1963; Basic Provisions of Construction and Installation Agreements, § 58, Monitor Polski No. 32, chapter 186 of 1958) is a damage deposit according to the general practices. Satisfying them does not exclude the possibility to claim an additional compensation for losses. The fundamental issue whether a contractual penalty is also due in cases where the debtors are not liable for the failure to fulfil their obligations according to the provisions of law has not yet unambiguously solved in Polish jurisprudence. The author deems that the circumstances releasing a debtor from the obligation to pay a penalty are not identical to the circumstances justifying the release of a debtor from liability (for failure to fulfil obligations) based on the general provisions on the contractual liability (Articles 239 — 242 of the Code of Obligations). Notwithstanding that, in most cases, the penalty is just a damage deposit for failure to fulfil obligations, it is still an independent legal institution. It can be due despite the absence of damage and, therefore, when there can be no question of liability for damages at all. It can also be due if the claim for this liability has already been satisfied; in this case, it is an additional obligation combined with full compensation for damages. The thesis about the contractual penalty independence from liability to recover damages due to the non-fulfilment of the obligations is confirmed in the resolutions concerning the Construction and Installation Agreements. According to the Basic provisions of the Agreements for these works dated 14 April 1958 (Monitor Polski, No. 32, chapter 186, § 58, sub-para 4 and 5), the obligation to pay a penalty becomes void only in three cases: 1) when the late performance of the obligation followed by the contractual penalty is due to the fault of the party entitled to the penalty, and when the non-fulfilment or improper fulfilment of the obligation is due to 2) a natural disaster * that has become an obstacle to the fulfilment of obligations, or 3) force majeure. Based on the analysis of the above three exempting circumstances, the author proves that a) the fault of the creditor is not equivalent to the concept of the creditor’s delay established by law, b) a natural disaster does not find an equivalent in the circumstances under the Code of Obligations excluding the liability of debtors who do not fulfil their obligations, c) force majeure, which, according to the provisions of the Code of Obligations, is a limit of special liability based on the moment of risk (Art. 150, 152), or liability enhanced or rather summarized as a result of assessment (Art. 415 § 2), constitutes the total limit of liability in the matter of contractual penalties binding in all cases. In fact, the Basic Provisions of Construction and Installation Agreements dated 1958 provide only one type of the contractual penalty — an offset. It means that the payment of this penalty is a contribution of advance damage deposit for non-fulfilment or improper fulfilment of the obligation, if the compensation for damages is generally due (and, therefore, if any damage occurs) and it is higher than the due amount paid in the form of the contractual penalty. Along with the offset principle, the author cites the following three general principles characterizing the penalty in the investment contracts: binding nature of the penalty, its bilateral nature and its establishment in writing. The first of them explains why a penalty is required by law, even if the text of a contract does not contain reference to it. The second principle is a consequence of the civil law nature of investment contracts and the equality of the parties which particularly demonstrates that the penalty for non-fulfilment of their obligations threatens any of them. The third principle is explained by the strict procedure for making contracts in writing that is used in the contractual system of the socialist economy, but its significance is to some extent relative due to the principle of binding nature of the penalty. Having considered the issue of the contractual penalties which burden the customer and contractors (general contractor and subcontractor), the author points to the “loopholes” in the Basic Provisions of Construction and Installation Agreements allowing them to escape their obligation to pay the penalty and withdraw from a contract (agreement). This refers to the provisions of § 62 sub-para 1 and 2, and § 66 of the Basic Provisions of Construction and Installation Agreements which, under certain conditions, provide for the following possibilities: a) contract change by the parties, in particular, by exempting them from the obligation to pay a penalty and extending the deadline for performance of work, and b) withdrawing from the contract. The author postulates the elimination of these loopholes, since they can lead to the weakening of the penalty effectiveness as a factor of strengthening the Investment discipline, and criticizes § 58 sub-para 3 of the Basic Provisions of Construction and Installation Agreements according to which a penalty is also due if “the obligation has not been fulfilled due to the decision of the higher body of the obligated party”. Such a decision can be qualified either as fait du prince or as the act of the third party. It should not cause negative economic consequences in the property of the debtors, such as hitting their self-financing. In conclusion, the author points out that the institution of a contractual penalty strengthens and expands the compensatory function of civil (property) liability for non-fulfilment or improper fulfilment of obligations but to a certain extent changes its nature by adding an element of property repression (penalty for act of omission that does not entail losses for the creditor) in certain situations. The institution of a contractual penalty as a tool for strengthening the investment discipline leads to a kind of “automation” of liability for failure to fulfil an obligation. However, this automation cannot facilitate the simplification of this liability and in particular cannot lead to a refusal to recover additional damages. The penalty should facilitate the performance of the compensatory and preventive function of liability but cannot completely replace or eliminate it. To fully use the institution of a contractual penalty as a factor of strengthening the investment discipline, it is required, in particular: 1) the establishment of penalties in the amount closest to the average loss caused by omission in the performance of certain duties associated with the penalty; 2) compliance with the obligation to collect penalties in all cases when they are due; 3) fulfilment of this obligation during the performance of work, and not after its completion; 4) specifying the terms and obligations of the parties in the provisions of the contract (agreement) as more specifically as possible in order to facilitate the implementation of the contractual penalties; 5) the scope of the contractual penalties; 6) the scope of the contractual penalties should not go beyond the fault of the working team; however, the fault should be understood broadly and cover all possible omissions in their work and organization to be avoided.